The Evolution of the Locoregional Therapy of Breast Cancer - Ho, Alice (AlphaMed Press, 2011)
Breast-conserving therapy (BCT) and mastectomy have equal survival outcomes. Rates of local recurrence after BCT have declined steadily, largely as a result of the widespread use of systemic therapy. Sentinel node biopsy has replaced axillary dissection for staging the axilla, and in women undergoing BCT with whole-breast irradiation (WBI), axillary dissection is not needed for local control or survival in those with fewer than three involved sentinel nodes. Alternatives to 6 weeks of WBI have been shown to be safe and effective for subsets of breast cancer patients, and the use of preoperative chemotherapy allows BCT in some women who require mastectomy if surgery is the initial step in treatment. The combination of the smaller cancers detected with screening and the routine use of multimodality therapy has resulted in a decrease in the morbidity of local therapy and improved cancer treatment outcomes.